2020
DOI: 10.1177/1057083720927748
|View full text |Cite
|
Sign up to set email alerts
|

Looking Within: An Investigation of Music Education Majors and Mental Health

Abstract: The primary purpose of this article was to establish the current state of mental health among music education majors. Music education majors across the United States ( N = 1137) self-reported indicators of depression, anxiety, and stress. According to the results, music education majors are highly busy, enrolling in an average of 16.5 credit hours (not including zero-credit courses) and rehearsing 9.75 hours a week; a majority of them also work for an average of 13 to 15 hours a week. Participants reported ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…This finding is in agreement with Koops and Kuebel (2019) who reported that a majority of music majors perceive themselves to have mild to extreme levels of anxiety, depression, and stress. Similarly, Kuebel (2019) and Payne et al (2020) noted that music education students, in particular, report high levels of anxiety and depression. Given these findings, I recommend that music faculty and music teacher educators help students to improve their mental health by providing structured support throughout every stage of the degree process, lessening the pressure of perfectionism that may be a byproduct of the conservatory-style approach of many music programs, reconceptualizing stressful situations as opportunities to improve, and implementing a plan of self-care.…”
Section: Implications For Music Teacher Educatorsmentioning
confidence: 91%
See 3 more Smart Citations
“…This finding is in agreement with Koops and Kuebel (2019) who reported that a majority of music majors perceive themselves to have mild to extreme levels of anxiety, depression, and stress. Similarly, Kuebel (2019) and Payne et al (2020) noted that music education students, in particular, report high levels of anxiety and depression. Given these findings, I recommend that music faculty and music teacher educators help students to improve their mental health by providing structured support throughout every stage of the degree process, lessening the pressure of perfectionism that may be a byproduct of the conservatory-style approach of many music programs, reconceptualizing stressful situations as opportunities to improve, and implementing a plan of self-care.…”
Section: Implications For Music Teacher Educatorsmentioning
confidence: 91%
“…Distress causes tension, nervousness, and fatigue that can adversely affect one's health (Hedden, 2005). Adequate sleep and GPA are both negatively correlated with anxiety and depression among music education students (Payne et al, 2020); therefore, students may alleviate distress by establishing healthy wellness behaviors related to sufficient sleep and academic success.…”
Section: Eustress and Distressmentioning
confidence: 99%
See 2 more Smart Citations
“…The perceived stress levels of these undergraduate students were higher than undergraduate students of other subject areas (Moore & Wilhelm, 2019). Payne et al (2020) surveyed music education majors across the United States to self-report indicators of depression, anxiety, and stress. Over half of the responses indicated moderate to severe depression (57%) and moderate to severe anxiety (70%).…”
mentioning
confidence: 99%